Pineapple Leaf Fiber Reinforced Polyester Composite Modified with Particles from Horse Dung Waste: Characterization of Mechanical Properties and Morphology - Nasmi Herlinasari; Suteja Suteja (Journal of Fibers and Polymer Composites, 2022)
Abstract. The modification of the characteristics of natural fiber composites with components derived from abundant and environmentally beneficial horse dung waste has piqued interest. The purpose of this investigation was to see how adding horse dung particles (DN) to pineapple leaf fiber (DN)/polyester composites affected the results. To create new samples, different percentages of HF (5–30%) are utilized. Hand-layup method was used to create the DN/HF composite. The results revealed that adding 30% (vol. percent) HF to the composite improved elongation, flexural strength, and flexural modulus, while adding 5% (vol. percent) HF improved impact strength, tensile strength, and tensile modulus of elasticity. At 30% HF concentration, maximum flexural strength values of 63.91 5.1 MPa were recorded. The composite's fracture morphology revealed weak interfacial interactions between DN-polyester-HF, and particle accumulation.